PENGARUH PRODUKTIVITAS PENGRAJIN BATIK TERHADAP KINERJA INDUSTRI SENTRA BATIK DESA KLAMPAR PADA MASA PANDEMI - Ika Oktaviana Dewi; Dewi Pusparini (BAJ: Behavioral Accounting Journal, 2021)
Productivity as a determining factor in achieving organizational goals, such as the batik industry to achieve goals must spur work productivity so that the performance of the batik industry increases indirectly. This study aims to determine the effect of work productivity on the industrial performance of the Klampar batik center. This research includes quantitative research. The sample selection used purposive sampling technique with sampling criteria, namely respondents who became owners and batik craftsmen, aged over 35 years with the number of batik produced in 1 month above 100 pieces of batik. The questionnaire was measured using a Likert scale. The results showed that there was a significant effect of the ability variable on industrial performance and the morale variable on industrial performance also had a significant effect, while the self-development variable had no effect on industrial performance. The existence of the Covid-19 pandemic does not reduce the ability and work spirit of batik craftsmen.